Radiography of the Distal Radius. (September 2021) - Gray, Robert R. L.; Foremny, Gregory; Lee, Susan; Greditzer, Tate
Abstract : Summary: Imaging of the distal radius is of paramount importance in diagnosing injuries, indicating patients for operative or nonoperative treatment, and appropriately following patients for associated injuries and complications. Plain radiographs and fluoroscopy are the dominant imaging modalities in all settings because they are readily available and provide valuable information about the osseous structures and any instrumentation. Computed tomography can offer more information about implant placement and the level of comminution of the articular surfaces but is more expensive and exposes patients to higher doses of radiation. Magnetic resonance imaging is less commonly used but is useful for occult fractures and other associated injuries. Ultrasonography is gaining popularity in evaluating implant placement, especially regarding tendon impingement and subsequent tendon injury. Abstract : Supplemental Digital Content is Available in the Text.